Alkaline phosphatase as a periodontal disease marker - Malhotra Ranjan; Grover Vishakha; Kapoor Anoop; Kapur Rupika (Wolters Kluwer Medknow Publications, 2010)
Background: The potential of alkaline phosphatase (ALP) as an important diagnostic marker of gingival crevicular fluid (GCF) has been the subject to investigation since 1970. ALP is stored in specific granules and secretory vesicles of the neutrophils and is mainly released during their migration to the site of infection. It is also present in bacteria within dental plaque, osteoblasts and fibroblasts. It has, thus, become important to elucidate whether GCF levels of ALP are potential measures of the inflammatory activity occurring in the adjacent periodontal tissues. Objective: The aim of this study was to assess the total activity of ALP in the GCF collected from healthy sites, sites with gingivitis and with chronic adult periodontitis. An attempt was also made to establish the correlation of ALP activity with plaque index, gingival index, bleeding index and probing depth. Materials and Methods: A total of 18 patients were divided into three groups: viz., healthy sites, Group I; gingivitis, Group II; chronic periodontitis, Group III. Clinical parameters like plaque index, bleeding index, gingival index and probing depth were recorded. The ALP level in GCF of all three groups was determined by spectrophotometric analysis. Results: Total enzyme activity of ALP was significantly higher in periodontitis as compared with that in healthy and gingivitis sites, and was significantly and positively correlated with probing depth. Conclusion: ALP can be considered as a periodontal disease marker as it can distinguish between healthy and inflamed sites. However, to better define its capacity for periodontal diagnosis, additional longitudinal studies are required.